Structure-function relationship of Rous sarcoma virus leader RNA. - Darlix, J L (1982)
Cells infected by RSV synthesize viral 35S RNA as well as subgenomic 28S and 22S RNAs coding for the Env and Src genes respectively. In addition, at least the 5' 101 nucleotides of the leader are also conserved and we have shown previously that this sequence contains a strong ribosome binding site (J.-L. Darlix et al., J. Virol. 29, 597). We now report the RNA sequence of Rous Sarcoma virus (RSV) leader RNA and propose a folding of this 5' untranslated region which brings the Cap, the initiation codon for Gag and the strong ribosome binding site close to each other. We also show that ribosomes protect a sequence just upstream from initiator Aug of Gag in vitro, and believed to interact with part of the strong ribosome binding site according to the folding proposed for the leader RNA.